Intellectual structure evolution of open access research observed through correlation index of keyword centrality - Cho, Jane (Scientometrics, 2020)
This study captured intellectual structures of open access by time frame using the pathfinder keyword network analysis method. 1998 papers published on Web of Science from 2005 to 2019 were divided into 3-year units, and keyword pathfinder networks were analyzed in five time segments. Thus, this study examined the time series changes of intellectual structure and keyword centrality. In addition, by analyzing the correlation index of keyword centrality between time segments, this study examined how long the similarities of the intellectual structure persisted and how it has changed. As a result, a weak correlation ( r = 0.10 ~ r = 0.49) was obtained from the observations in 2005 for 9 years; however, the correlation decreased sharply since 2014 ( r = − 0.06 ~ r = 0.00). New research topics have emerged that have not been highlighted in centrality, such as article processing charge, altmetrics, and research data. The scope of research has changed as subjects such as document delivery that showed high centrality initially, disappeared.